Design and implementation of big data visualization for student housing analysis / Khairul Anwar Sedek ... [et al.] - Sedek, Khairul Anwar; Mohd Maulus, Nurfarah Fatini; Osman, Mohd Nizam; Othman, Nor Arzami (Faculty of Information Management, 2023)
The Student Affairs Division of UiTM Perlis is responsible for nonacademic matters. However, the current e-Kolej system lacks comprehensive residential data, making it impossible for staff and students to analyse and use the data effectively. The purpose of this study is to address this issue by developing a residential dashboard that provides the platform for college statistics. By providing staff members with access to and analysis of relevant data, the dashboard will support informed decision-making and efficient management of student housing. The phases of the project include a requirements analysis, design, implementation, and usability assessment. This method employs Apache Hive for large data warehouses, HiveQL for data analytics, and Microsoft Power BI for data representation. Thirty participants provided valuable feedback during the test, validating the dashboard's usability and effectiveness in providing users with the required data. According to the evaluation data, the average overall score is 4.71. Future projects include adding more information from other perspectives to the dashboard and integrating the dashboard with the college database system at UiTM Perlis Branch remain.